FIGURE 2 in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 2. Some intertidal habitats on Trindade Island. A, C, F, Parcel das Tartarugas: A, C, May 2012. F, June 2016. B, D, Praia dos Andradas, May 2012. E, Praia das Tartarugas (Parcel das Tartarugas can be seen in the horizon), May 2012. Photographs by J.B. Mendonça. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 8, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155